Corporate carbon emissions management and the disclosure of key audit matters - Wang, Guoqing; Wu, Maoguo (Frontiers in Environmental Science, 2024)
The principle that sustainable development can foster high-quality corporate growth has gained popularity as a tool for environmental protection. Utilizing data of firms listed on Shanghai Stock Exchange and Shenzhen Stock Exchange from 2010 to 2020, this study investigates the impact of corporate carbon emissions management (CCEM) on the disclosure of key audit matters (KAMs). The findings indicate that CCEM can significantly elevate the adequacy of disclosure concerning KAMs. Tests on underlying mechanism underscore that accounting conservatism and audit quality serve as pivotal channels through which CCEM facilitates the disclosure of KAMs. Further analysis on economic consequences reveals that the disclosure of KAMs helps mitigate stock price crash risk while enhancing environmental, social, and governance performance. This study enriches research on factors influencing the disclosure of KAMs, concurrently providing valuable insights for advancing high-quality corporate development and facilitating communication between auditors and users of audit reports.Keywords: corporate carbon emissions management, disclosure of key audit matters, accounting conservatism, audit quality 1 The 1 in the "1+N" policy framework refers to the "Opinions on Working Actively and Prudently toward the Goals of Reaching Carbon Emissions Peaking and Carbon Neutrality" issued at the policy level, while N includes the action program for carbon emissions peaking by 2030 and policy measures and actions in key areas and industries to be gradually implemented in the future. The "1+N" policy framework clarifies the main objectives, carbon reduction pathways, and relevant supporting measures from the top-level design, and provides policy support for the future carbon emissions peaking and carbon neutrality action program, as well as policy measures and actions in key areas and industries.